Investigating Causes of Delays in Iranian Construction Industry According to Project Delivery Methods - Ghasemzadeh, Borhan (Eastern Mediterranean University (EMU) - Doğu Akdeniz Üniversitesi (DAÜ), 2014)
ABSTRACT: Construction delays can be defined as the late completion of work compared to the planned schedule or contract schedule. Construction delays can be minimized only when their cause are identified. The objective of this study was to identify the major causes of construction delays and the effects of those delays in Iranian construction industry. Also in this research the relation between project delivery method and these delays has been discussed to achieve the best and most suitable method according to the situation in Iran. This study was carried out based on literature review and a questionnaire survey. A total of six groups were contributed to the identification of causes of construction delays including clients, contractors, consultants, public authorities, contractual relationship delay and external parties. The questionnaires were distributed to the target respondents in Iranian construction industry. The most important factors that contributed to the causes of delays were related to financial problems such as delay in progress payments by owner or difficulties in financing project by contractor. Alongside of these problems, the inflation has also high influence on delay and it is because of political and economical situation of Iran. Client-related delays were ranked the most significant groups that cause delays, followed by contractor-related delays, and public authorities-related delays. Time and cost overrun were the common effects of delays in construction projects and unfortunately most of Iranian companies did not pay attention to the causes of delay till they happened and usually they do not employ professional construction manager in this specific field during the construction phase of the projects. Keywords: Project Delivery Method, Delay, Iranian Construction Industry. ………………………………………………………………………………………………………………………… ÖZ: İnşaat gecikmeleri planlanan program veya sözleşme takvimine göre işin geç tamamlanması olarak tanımlanabilir. İnşaat gecikmeleri tespit edildikten sonra azaltabilir. Bu çalışmanın amacı inşaat gecikmelerinin başlıca nedenleri ve İran inşaat sektöründe bu gecikmelerin etkilerini belirlemektir. Ayrıca bu araştırma, proje teslim yöntemi ve bu gecikmeler arasındaki ilişki İran'daki duruma göre en iyi ve en uygun yöntemi ulaşmak için ele alınmıştır. Bu çalışma, literatür taraması ve ankete dayalı yürütülmüştür. Toplam altı grupta müşteriler, yükleniciler, danışmanlar, kamu yetkilileri, sözleşme ilişkisi gecikme uzmani ve dış elemanlari dahil, inşaat gecikme nedenlerinin belirlenmesine katkıda bulunmuştur. Anketler İran inşaat sektöründek, hedef katılımcılara dağıtıldı. Gecikme nedenlerinin en önemli faktörleri mali problemlerden kaynaklaniyor ve mal sahibi odemelerde geçiktiği zaman veya yüklenici tarafından finansman projesinde zorluklar çıkması gibi konulardenidi. Bu sorunların yanı sıra, enflasyonun yüksek bir etkisi vardır ve bunun nedeni İran'ın siyasi ve ekonomik durumundan bayraklenecektedir. Müşteriler ile ilgili gecikmeler müteahhitler’le ilgili gecikmelere en önemli neden kamu otoritelerindeki gecikmeleri olduğu belirlendi. Zamaninde tamamlanımı ve maliyetler inşaat projelerinde gecikmeler, ortak etkiler İran şirketlerinin çoğu gecikme nedenlerine dikkat etmediği ve genellikle inşaat projelerin aşamasında bu özel alanda profesyonel inşaat yöneticisi istihdam olmadiğinda sorun yaşadığı güzlemlenmıştır. vi Anahtar kelimeler: Proje Teslim Şekli, Gecikme, İran İnşaat Sanayi.
Master of Science in Civil Engineering. Thesis (M.S.)--Eastern Mediterranean University, Faculty of Engineering, Dept. of Civil Engineering, 2014. Supervisor: Assist. Prof. Dr. Alireza Rezaei.
Keywords: Civil Engineering; Construction projects - Iran; Construction industry - Management - Production scheduling - Construction projects; Project management; Project Delivery Method, Delay, Iranian Construction Industry